2002
DOI: 10.1063/1.1466528
|View full text |Cite|
|
Sign up to set email alerts
|

Band gap in epitaxial NaCl-structure CrN(001) layers

Abstract: B1-NaCl-structure CrN͑001͒ layers were grown on MgO͑001͒ at 600°C by ultrahigh vacuum reactive magnetron sputter deposition in pure N 2 discharges. X-ray diffraction analyses establish the epitaxial relationship as cube-on-cube, (001) CrN ʈ (001) MgO with ͓100͔ CrN ʈ ͓100͔ MgO , while temperature-dependent measurements show that the previously reported phase transition to the orthorhombic P nma structure is, due to epitaxial constraints, absent in our layers. The resistivity increases with decreasing temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
88
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 32 publications
12
88
3
Order By: Relevance
“…Adding N vacancies and/or other defects coupled with a narrow band gap will increase the charge carrier density resulting in metallic conducting properties [15][16][17]. Gall et al [18] measured an optical band gap of approximately 0.7 eV and conclude that the semiconducting properties stem from the existence of magnetic moments and the Hubbard energy rather than the crystal structure, indicating a Mott insulator.…”
Section: Introductionmentioning
confidence: 99%
“…Adding N vacancies and/or other defects coupled with a narrow band gap will increase the charge carrier density resulting in metallic conducting properties [15][16][17]. Gall et al [18] measured an optical band gap of approximately 0.7 eV and conclude that the semiconducting properties stem from the existence of magnetic moments and the Hubbard energy rather than the crystal structure, indicating a Mott insulator.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Considerable experimental and theoretical work have demonstrated that CrN undergoes a magnetic and structural phase transition from a paramagnetic NaCl structure at room temperature to a low-temperature antiferromagnetic orthorhombic P nma phase at N eel temperature of 273-286 K. [5][6][7] A variety of electrical transport properties in CrN have been observed, such as, a semiconducting behavior with dq/dT < 0, [8][9][10][11] a metallic behavior with dq/dT > 0, [12][13][14] and continuous and discontinuous q(T) curves at 260-280 K. [8][9][10][11][12][13]15 These differences in electrical transport properties have been attributed to the sensitivity of the transport properties to N stoichiometry. 12,15 In addition, the discontinuity in q(T) curves has usually been observed in CrN powders or polycrystalline CrN films, rather than in epitaxial films, suggesting that the epitaxial constraints could affect the transition.…”
Section: Introductionmentioning
confidence: 99%
“…MgO has a lattice mismatch of ¹1.7% with respect to CrN. Preparation of epitaxial CrN thin films on MgO(100) substrates to evaluate electronic and magnetic properties has been reported by Ney et al, 17) Gall et al, 18,19) Constantin et al 20) and Inumaru et al 21) However, preparation of epitaxial Cr(N,O) thin films and their evaluation for oxidation behavior have not been previously reported. We attempted preparation of epitaxial Cr(N,O) thin films on MgO substrates and carried out oxidation tests in air using these thin films.…”
Section: Introductionmentioning
confidence: 99%